PENGEMBANGAN MODUL MATEMATIKA BERILUSTRASI KOMIK PADA MATERI SKALA DAN PERBANDINGAN KELAS VII SMP/MTs - Ariastutik, Endah; Kusmayadi, Tri Atmojo; Sujadi, Imam (Journal of Mathematics and Mathematics Education, 2016)
Abstract: This study aims at: 1) investigating elegibility of comic-illustrated mathematics module on the materials of scale and comparison for grade VII students of SMP/MTs, 2) investigating the effectiveness of comic-illustrated mathematics module on the materials of scale and comparison for grade VII students of SMP/MTs. This study was a research and development (R & D) in mathematics learning at SMP/MTs. The applied development model was a development model postulated by Borg and Gall modified by Sukmadinata, which consists of three stages, including: 1) preliminary research, 2) development, and 3) field testing, each of which contains several steps. The product validation process was carried out by material experts, media experts, and respondents. The effectiveness testing for the module carried out in MTs Negeri Ngawi. The data collecting instrument used was the mathematics performance test. The content validity was measured by validators. The reliability test for measuring the test instrument applied KR-20 formula and the discriminatory power used product-moment correlation formula by Karl Pearson. The balance test was carried out by using t-test. The prerequisite tests covered normality test using Lilliefors testing method and homogeneity test using Barttlet method. The experimental design for this research was randomized post-test-only control group design. On the basis of the research findings and development, the research is concluded: 1) the comic-illustrated mathematics module was feasible to be used in learning process, the comic-illustrated mathematics module is considered feasible when the evaluation result from retriever is “good”, 2) the average students learning achievement in experiment class is better than that in control class, this conclusion is in accordance with the hypotheses proposed, namely learning with comic-illustrated mathematics module on the materials of scale and comparison for grade VII of SMP/MTs is more effective than direct learning without comic-illustrated mathematics module.Keywords: Learning Module, Mathematics Comic, Scale and Comparison.